Analisis Kemampuan Berpikir Kreatif Anak Pada Pengaplikasian Tower Crane Ditinjau Dari Gaya Belajar - Retno Cahyanti; Nurina Happy; Lilik Ariyanto; Bungkus Dias (Departement of Mathematics Education, 2024)
This research aims to determine the ability to think creatively through the application of a tower crane. The type of research used in this research is descriptive qualitative. This research was conducted in STEM Village, Joho, Yogyakarta. The subjects in this study consisted of 4 children. Data collection through observation techniques, interviews and questionnaires. Based on research on children's creative thinking abilities in STEM village, Joho, Yogyakarta. It was found that the tower crane application activity was able to determine children's creative thinking. The research results show the ability to think creatively based on learning styles during the Tower Crane application project. Two children with an auditory learning style were able to meet the indicators for fluent thinking (Fluency) and flexible thinking (Flexibility). Two children with a visual learning style were able to meet the indicators of creative thinking, namely Fluency and Originality.